ANALISA KETERKAITAN ANTARA INDIKATOR, TUJUAN PEMBELAJARAN, MATERI, DAN EVALUASI DALAM RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MATA PELAJARAN BIOLOGI GURU SMA NEGERI DAN SWASTA DI KOTA PADANG - Afshillah, Egi; Mulyati, Mulyati; Risdawati, Renny (STKIP PGRI Sumbar, 2013)
ABSTRACT This research aims to know relation of indicator, learning objectives, material and evaluation in lesson plan biology of state and private senior high school teachers in Padang. This research was a descriptive research. The research population was lesson plan that designed by state and private senior high school teachers in Padang teach at first semester of first grade, academic year 2012/2013 amount sixteen lesson plan of state senior high school and thirty two lesson plan of private senior high school. The result of this research showed teachers lesson plan in completed criteria component of lesson plan which made by teacher state and private senior high school in Padang is 91,15% in good category. Percentage result of relation of indicator, learning objectives, material and evaluation overall is 76% with relation category that good enough.